Improving Student Mental Health in an Islamic Boarding School through ABCD-Based Helping Adolescents Thrive Training - Risnah Risnah; Djuwairiah Ahmad; Auliya Indah Fauzian; Nur Fathihurresky Mirsan; Muhammad Irwan; Sari Rahayu Rahman (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Adolescent mental health is receiving growing attention across sectors, including within Islamic boarding schools (pesantren). As faith-based educational institutions, pesantren are well positioned to support students’ psychological development; however, adolescents in these settings may face stressors related to academic demands, social adjustment, and communal living. This program implemented Helping Adolescents Thrive (HAT) training using an Asset-Based Community Development (ABCD) approach to strengthen students’ life skills, emotional regulation, and resilience. The intervention used interactive lectures, guided discussions, and simulations and was delivered to female students at Darul Aman Islamic Boarding School. Implementation occurred in three stages: (1) identification and mapping of community assets within the pesantren, (2) delivery of HAT training aligned with those assets, and (3) evaluation of program impact. Findings indicatedimproved participant understanding of mental health and positive changes in self-concept. The ABCD framework also appeared to increase students’ confidence in addressing challenges and their openness to seeking support when experiencing psychosocial difficulties. Overall, ABCD-informed HAT training shows promise for promoting adolescent mental health in pesantren settings, although additional multi-site evaluations are needed to assess broader applicability.